Bioethical aspects of prenatal diagnosis - Karaboue, Karidia (Medicina Historica, 2023)
Prenatal diagnosis has become both a requirement and right for women, regardless of its medical practicalities or reasons. It is frequently observed that women choose to undergo prenatal checks, actively participating in the reproduction of their society’s culture and thus often considering themselves feminists i.e., women who have taken their lives into their own hands. According to some observers, this process has now been taken to excess and that from its use as a valuable cognitive procedure, prenatal diagnosis has rapidly developed into a tool for prenatal selection. A qualitative judgement is always given, starting from the 'vision' of a phantom created using technical instruments. It is as if the outcome of an examination assigns a higher or lower value to the life of an unborn child, with consequent psychological repercussions given the symbolic power of reproductive technologies used on women. The opportunities offered by diagnosis may generate new desires but also lead to new fears and a drive for measures aimed to avert them, resulting in physical pathologies and social imbalance.